Reversing fertility decline in Japan with foreign pro-natalist policies, 1990–2035: a systematic review and secondary data analysisResearch in context - Md Mizanur Rahman; Haruka Sakamoto; Sabera Sultana; Miho Sassa; Md Ashraful Alam; Kenji Shibuya (The Lancet Regional Health. Western Pacific)
Summary: Background: Several high-income countries, including Japan, have adopted pro-natalist policy to counteract declining fertility rates. However, the effectiveness of these policies varied across different studies and countries. This study aims to conduct an initial systematic review to identify effective policies that have reversed declining fertility rates. Subsequently, it will apply them to Japan’s context through scenario-based secondary analysis. The goals are to project Japan’s total fertility rate (TFR) up to the year 2035. Methods: We conducted searches in major electronic databases from their inception until March 27 2025 to investigate the impact of fertility policies. We also extracted a variety demographic and public expenditure data from the OECD, World Bank, and IMF databases for the years 1990–2022. A Bayesian hierarchical regression model was used to estimate and project Japan’s TFR trends up to 2035 in Japan, analyzing the effects of significant fertility policies on these trends. Findings: Our analysis included a total of 61 studies focusing on pro-natalist policies, identifying cash benefit policies—such as payment at birth, allowances, paid maternity and paternal leave, childcare coverage, and tax exemptions—as the most influential. Unpaid maternity leaves, universal two-child policy, and Assisted Reproductive Technology health insurance coverage also showed potential to boost fertility, although further research is needed. Countries like Australia, Greece, Hungary, France, and the UK allocate over 1.3% of their GDP to family cash benefits, contrasting Japan and Korea, where the allocation is less than 1%. Our findings indicate that Japan’s current cash benefit policies are unlikely to significantly reverse the fertility decline by 2030 (12% likelihood) and 2035 (29% likelihood). However, should Japan enhance its cash benefits to levels observed in Australia, Hungary, and France by 2030, the probability of reversing Japan’s fertility decline could rise significantly to 79%, 70%, and 69%, respectively. Even if cash benefit policies are scaled up by 2035, the probability of reversing the decline fertility rate is projected to be around 60 or more. Interpretation: Cash benefits emerged as the most effective fertility policy in high-income countries, although such benefits in Japan were notably modest. Elevating Japan’s cash benefit scheme could potentially lead to higher TFR. Funding: HIAS Health, Hitotsubashi University; Tokyo Foundation for Policy Research, Japan.